2019
DOI: 10.2147/ott.s181432
|View full text |Cite
|
Sign up to set email alerts
|

<p>PAQR4 promotes cell proliferation and metastasis through the CDK4-pRB-E2F1 pathway in non-small-cell lung cancer</p>

Abstract: Background It is reported that progestin and adipoQ receptor 4 (PAQR4) has a tumorigenic effect on human breast cancer, but the role of PAQR4 in non-small-cell lung cancer (NSCLC) is unknown. The aim of this study was to investigate the role of PAQR4 in NSCLC. Methods Quantitative real-time PCR (qRT-PCR) and immunohistchemical (IHC) staining were used to analyze the expression of PAQR4 in HCC tissues and adjacent normal tissues. MTT, colony formation assay, flow cytomet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 23 publications
2
10
0
Order By: Relevance
“…al. (Wang et al, 2017;Wu and Liu, 2019;Zhang et al, 2018), we find that PAQR4 reduces cancer cell growth. Their studies suggest that PAQR4 controls cellular growth through stabilization of cyclin-dependent kinase 4 (CDK4) and hence cell cycle state.…”
Section: Discussionsupporting
confidence: 54%
“…al. (Wang et al, 2017;Wu and Liu, 2019;Zhang et al, 2018), we find that PAQR4 reduces cancer cell growth. Their studies suggest that PAQR4 controls cellular growth through stabilization of cyclin-dependent kinase 4 (CDK4) and hence cell cycle state.…”
Section: Discussionsupporting
confidence: 54%
“…Besides, Zhang et al (2018) demonstrated that PAQR4 exert its oncogenic role in breast cancer through inhibiting CDK4 degradation. Moreover, PAQR4 promoted cell growth, metastasis, and chemoresistance in non-small-cell lung cancer ( Wu and Liu, 2019 ; Xu et al, 2020 ). Combing to our KEGG results of RNA-seq in circNOLC1 overexpression, we assumed that circNOLC1 activates PI3K/Akt pathway in PCa via a miR-647/PAQR4 axis.…”
Section: Discussionmentioning
confidence: 99%
“…PAQR4 has a tumorigenic effect on human breast cancers, and such effect is associated with a modulatory activity of PAQR4 on protein degradation of CDK4 [40,41]. PAQR4 promotes cell proliferation and metastasis in both non-small-cell lung cancer [42] and gastric cancer [43]. C21orf58 exerts a momentous effect on breast cancer cell growth [14].…”
Section: Discussionmentioning
confidence: 99%